A Qualitative Review Of Game Theory Models In Market Transactions - Benardi Benardi; Tanti Sugiharti; A. Sigit Pramono Hadi (LPPM STIE Kasih Bangsa, 2024)
This study is a qualitative review of game theory models in market transactions, focusing on the dynamics of matching between agents with diverse preferences. By examining various recent literatures, this research identifies two competition regimes in the market related to connectivity levels, namely